The Galaxy Zoo survey for giant AGN-ionized clouds: past and present black-hole accretion events - Keel, W; Chojnowski, S; Bennert, V; Schawinski, K; Lintott, C; Lynn, S; Pancoast, A; Harris, C; Nierenberg, A; Sonnenfeld, A; Proctor, R (2011)
Some active galactic nuclei (AGN) are surrounded by extended emission-line regions (EELRs), which trace both the illumination pattern of escaping radiation and its history over the light-travel time from the AGN to the gas. From a new set of such EELRs, we present evidence that the AGN in many Seyfert galaxies undergo luminous episodes 20,000-200,000 years in duration. Motivated by the discovery of the spectacular nebula known as Hanny's Voorwerp, ionized by a powerful AGN which has apparently faded dramatically within ~ 100,000 years, Galaxy Zoo volunteers have carried out both targeted and serendipitous searches for similar emission-line clouds around low-redshift galaxies.We present the resulting list of candidates and describe spectroscopy identifying 19 galaxies with AGN-ionized regions at projected radii > 10 kpc. This search recovered known EELRs and identified additional previously unknown cases, one with detected emission to r = 37 kpc. At least 14/19 are in interacting or merging systems; tidal tails are a prime source of extraplanar ionized gas. We see a mix of one- and two-sided structures, with observed cone angles from 23-112 degrees. We consider the energy balance in the ionized clouds, with lower and upper bounds on ionizing luminosity from recombination and ionization-parameter arguments, and estimate the luminosity of the core from the far-infrared data. The implied ratio of ionizing radiation seen by the clouds to that emitted by the nucleus, for a constant nuclear source, ranges from 0.02 to > 12; 7/19 exceed unity. Small values imply heavily obscured AGN. However, large values may require that the AGN has faded over tens of thousands of years, giving us several examples of systems in which such dramatic long-period variation has occurred; this is the only current technique for addressing these timescales in AGN history. (Abridged)